Legal Literacy Field School as An Innovation in Promoting Legal Awareness for Vocational High School Students - Dito Aditia; Muhimah, Uum Ummul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to explain the implementation of a legal literacy field school to increase legal awareness among students at SMK Unggulan Al Manar Tajinan and to develop an innovative concept for legal literacy field schools through an action plan. Design/Methodology/Approach – This study employs a descriptive method with a systematic literature review approach as the philosophical basis for developing the field school innovation. The program implementation uses learning methods consisting of Direct Class and Reflective activities, covering 12 lessons that develop three competencies: cognitive, affective, and psychomotor aspects related to legal literacy, legal awareness, communication, entrepreneurship, and innovation. Findings – The results show that the legal literacy field school can instill legal awareness and initiative among vocational high school students. The study proposes an action plan consisting of Planning, Strategizing, Organizing, Actuating, Controlling, and Evaluating (PSOACE) to ensure sustainable implementation and broader community impact in improving legal awareness. Originality/Value This research provides value by introducing an innovative legal literacy field school model supported by a systematic action plan, integrating cognitive, affective, and psychomotor competencies. It offers a practical framework that can be replicated to enhance legal awareness in broader educational and community contexts.